The relation between the presence of cardiovascular disease and vascular risk factors in offspring and the occurrence of new vascular events in their parents already at high vascular risk - Weijmans, Maaike; Van Der Graaf, Yolanda; De Borst, Gert Jan; Asselbergs, Folkert W.; Cramer, Maarten Jan; Algra, Ale; Visseren, Frank L J (Elsevier, 2015)
Background For parents at high risk for cardiovascular events, presence of cardiovascular disease or risk factors in their offspring may be an indicator of their genetic load or exposure to (unknown) risk factors and might be related to the development of new or recurrent vascular events. Methods In 4,267 patients with vascular disease, hypertension, diabetes, or hypercholesterolemia enrolled in the SMART cohort, the presence of cardiovascular risk factors (hypertension, diabetes, hypercholesterolemia, smoking, or overweight) and cardiovascular disease (coronary artery disease, cerebrovascular disease, peripheral artery disease, or abdominal aortic aneurysm) was assessed in their 10,564 children. The relation between presence of cardiovascular disease or cardiovascular risk factors in their offspring and new or recurrent vascular events was determined by Cox proportional hazard analyses. Results Of the patients, 506 (12%) had offspring with cardiovascular disease, hypertension, hypercholesterolemia, or diabetes. Smoking in offspring was present in 1,972 patients (46%), and overweight in 845 patients (20%). During a median follow-up of 7.0 years (interquartile range 3.7-10.4), the composite outcome of myocardial infarction (MI), stroke, or vascular mortality occurred in 251 patients. Patients with offspring with cardiovascular disease, hypertension, hypercholesterolemia, or diabetes had an increased risk of vascular mortality (hazard ratio [HR] 2.9, 95% CI 1.2-7.1), MI (HR 1.6, 95% CI 1.1-2.5), and the composite outcome (HR 1.5, 95% CI 1.1-2.2). Diabetes in offspring was related to an increased risk of the composite outcome (HR 2.7, 95% CI 1.5-5.0), MI (HR 3.3, 95% CI 1.7-6.6), and vascular mortality (HR 3.4, 95% CI 0.8-14.8). Smoking and overweight in offspring were not related to increased vascular risk in parents. Conclusions Presence of cardiovascular disease, hypertension, hypercholesterolemia, and diabetes in offspring, with diabetes mellitus being the most contributing cardiovascular risk factor, is related to an increased risk of developing new or subsequent vascular events in patients already at high vascular risk.
Keywords: CORONARY-HEART-DISEASE; ARTERIAL-DISEASE; HISTORY; SCORE; PREDICTION; VALIDATION; MORTALITY; SURVIVAL; TRENDS; SMART; Taverne; Cardiology and Cardiovascular Medicine